2022
DOI: 10.1136/bmjopen-2021-054783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the willingness and influencing factors of choosing primary healthcare institutions among patients with chronic conditions in China: a cross-sectional study

Abstract: ObjectiveTo assess the willingness and factors influencing the choice of primary healthcare (PHC) institutions among patients with chronic conditions in China.DesignA nationwide population-based study with binary logistic regression was conducted and used to estimate the ORs of the influencing factors of health-seeking at PHC institutions using the Anderson model as a theoretical framework.SettingThe China Family Panel Studies (CFPS) database.ParticipantsThe study sample included 7967 patients with chronic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This study revealed that older patients and those with a lower income are more likely to take community-based primary care facilities as a first choice for medical attention. These results are consistent with the findings of previous studies [ 30 32 ]. Obviously, financial concern has continued to play an important role in the patient choice of care providers despite near universal coverage of social health insurance programs in China [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study revealed that older patients and those with a lower income are more likely to take community-based primary care facilities as a first choice for medical attention. These results are consistent with the findings of previous studies [ 30 32 ]. Obviously, financial concern has continued to play an important role in the patient choice of care providers despite near universal coverage of social health insurance programs in China [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…As a result, the convenience and accessibility advantages offered by primary health care institutions will no longer be evident. There is an urgent need to improve their ability to attract patients 12 . Nonetheless, this also contradicts some of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study employed the Anderson behavioural model as a theoretical framework to assess the desire and determinants influencing the selection of hospice facilities among the elderly population in China, with the aim of providing recommendations for further enhancing the growth of hospice care institutions. Andersen’s behavioural model of health service utilisation was initially developed in the late 1960s and serves as a theoretical framework for analysing the factors that influence medical service utilisation 16. As many countries are yet to establish a robust hospice care system, our study can offer valuable insights into how such systems can be developed and tailored according to each country’s unique cultural context and healthcare infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen’s behavioural model of health service utilisation was initially developed in the late 1960s and serves as a theoretical framework for analysing the factors that influence medical service utilisation. 16 As many countries are yet to establish a robust hospice care system, our study can offer valuable insights into how such systems can be developed and tailored according to each country’s unique cultural context and healthcare infrastructure. By delving deeper into these factors, we aim not only to provide recommendations for further enhancing the growth of hospice care institutions in China but also contribute towards fostering a more compassionate and supportive environment globally for individuals approaching the end of life.…”
Section: Introductionmentioning
confidence: 99%